Laparoscopic Versus Open Complete Mesocolic Excision with Central Vascular Ligation for Right-sided Colon Cancer: Early Postoperative Outcomes - Lale, Azmi; Karahan, Veysel; Kırmızı, İlter; Küçükdiler, Engin; Aslan, Ahmet; Yur, Mesut; Aygen, Erhan (Galenos Publishing House, 2022)
Aim: To evaluate postoperative histopathological findings and short-term clinical outcomes of laparoscopic complete mesocolic excision (L-CME) versus open-complete mesocolic excision (O-CME) for right-sided colon cancers. Method: A total of 36 eligible patients were included. Patients were divided into two main groups as L-CME (n=21) and O-CME (n=15). Demographic parameters, intraoperative findings, early postoperative outcomes and histopathological findings were compared between the groups. Results: Age, sex, body mass index, American Society of Anesthesiology scores, comorbid diseases, neoadjuvant treatment, carcinoembryonic antigen level, and tumor locations were similar in L-CME and O-CME groups. tumor, node, and metastasis stage, mean proximal and distal surgical margin distances, and mean total retrieved lymph nodes (L-CME: 27.9 vs O-CME: 28.4; p=0.368) were similar between the groups. Duration of operation (L-CME: 171.9 vs O-CME: 164.7 minutes; p=0.287), estimated blood loss (L-CME: 130 vs O-CME: 143.3 mL; p=0.508), length of hospital stay (L-CME: 8.6 vs O-CME: 11.5 days; p=0.936), intraoperative complication rates, postoperative non-surgical complication rates (L-CME: 4.8% vs O-CME: 20.0%; p=0.214), postoperative mortality rates (L-CME: 0.0% vs O-CME: 13.3%; p=0.085), and re-operation rates (L-CME: 4.8% vs O-CME: 6.7%; p=0.806) were also similar between the groups. First flatus time was shorter (L-CME: 2.5 vs O-CME: 2.9 days; p=0.038), postoperative surgical complication rate was less (L-CME: 14.3% vs O-CME: 53.7%; p=0.008), overall postoperative 30-day complication rates were less (L-CME: 14.3% vs O-CME: 60.0%; p=0.004), and the severity of complications were less (p=0.016) in L-CME group. Conclusion: L-CME is technically feasible and safe for right colon cancers. It appears to be non-inferior to O-CME in terms of harvested lymph nodes and it provides faster postoperative recovery. © Copyright 2022 by Turkish Society of Colon and Rectal Surgery.
Keywords: central vascular ligation; complete mesocolic excision; D3 lymph node dissection; Laparoscopic right hemicolectomy; right colon cancer